Potensi Hijauan dan Limbah Pertanian Tanaman Pangan Sebagai Pakan Ruminansia di Kabupaten Seram Bagian Barat - Telupere, Nova S H; Salamena, Jerry F; Puturuhu, Ferad (Universitas Pattimura, 2021)
The availability of animal feed is one of the main problems faced in livestock development efforts. This research was carried out from August to September 2018, with the aim of identifying and knowing the potentials of forages and food crop agricultural wastes as ruminant animal feed, as well as determining the regional capacity for ruminant livestock in Western Ceram Regency. The research method used was a survey method through direct observation and measurement in the field. Determination of sampling locations was carried out using purposive sampling involving three sample sub-districts, namely in Kairatu, West Kairatu and West Ceram sub-districts. Measurement variables included forage types, botanical composition and pasture holding capacity, as well as agricultural waste holding capacity. The results of the research showed that the dominant grass species in the pastures were carpet grass (Axonopus compresus) 23.39%, sedge (Cyperus rotundus) 7.34%, and the least were 'cunchurs' and 'rozi' grasses 1.27%. The pasture botanical composition was a mixture of legumes, grasses and weeds, with a ratio of grass 83.77%: legumes 7.8%: weeds 8.43%. The average carrying capacities of ruminant livestock units (LU) on pastures in the three sample sub-districts were: Kairatu 2.18 ha/LU/year (0.46 LU/ha/year), West Kairatu 2.18 LU/ha/year (0.46 LU/ha/year) and West Seram 2.67 ha/LU/year (0.37 LU/ha/year) and the average capacity in Wester Ceram Regency was 7.03 ha/LU/year (0 .14 LU/ha/year). Types of potential agricultural waste in West Ceram Regency were rice straw 7.97 tons/year, corn straw (zea mays) 487.20 tons/yea, cassava waste 129.40 tons/year and sweet potato waste 47 tons/year. In general, the holding capacity of pasture in Western Ceram Regency was lower compared to the natural grass holding capacity for the Maluku area of ​​4 LU/ha/year.